MENINGKATKAN KEMAMPUAN MENYIMAK ANAK USIA 5-6 TAHUN MELALUI METODE BERCERITA DENGAN MEDIA WAYANG KERTAS DI TK KASIH IBU KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR - Diana Febrianti; Isjoni Isjoni; Yeni Solfiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the increase listening skills in children aged 5-6 years through storytelling with puppets media paper in kindergarten Kasih Ibu District XIII Koto Kampar Kampar regency. This study is kind studies using action research or (PTK) is conducted in two cycles. Each cycle consists of planning, action planning, observation / evaluation and reflection. Subject empirically n are children in group B who are 20 children in kindergarten Kasih Ibu. The research data obtained through observation and data analysis was done by using quantitative descriptive analysis. The research shows that the method of storytelling with puppets media paper can improve listening skills in children ages 5 -6 years. It can be seen from the increase in the average percentage of listening skills of children in the first cycle of 52.4% which is the criteria began to develop (MB) and an increase of 50% in the second cycle be 77.5% which is very good at developing criteria (BSB). Thus, the method bercereita using paper puppets media can improve listening skills of children ages 5 -6 years in kindergarten Kasih Ibu District XIII Koto Kampar Kampar regency.Keywords : Listening ability, Method Media Storytelling with Puppets Paper